Neuropharmacological Assessment of Sulfonamide Derivatives of Para-Aminobenzoic Acid through In Vivo and In Silico Approaches - Ankit Ganeshpurkar; Ravi Singh; Pratigya Tripathi; Qadir Alam; Sairam Krishnamurthy; Ashok Kumar; Sushil Kumar Singh (Drugs and Drug Candidates)
Background/Objectives: Alzheimer’s disease (AD), a complex neurogenerative disorder, manifests as dementia and concomitant neuropsychiatric symptoms, including apathy, depression, and circadian disruption. The pathology involves a profound degeneration of the hippocampus and cerebral cortex, leading to the impairment of both short-term and long-term memory. The cholinergic hypothesis is among the various theories proposed, that assume the loss of the cholinergic tract contributes to the onset of AD and proves clinically effective in managing mild to moderate stages of the disease. This study explores the potential therapeutic efficacy of sulfonamide-based butyrylcholinesterase inhibitors in mitigating scopolamine-induced amnesia in rats. Methods: Behavioral assessments utilizing Y-maze, Barnes maze, and neurochemical assays were conducted to evaluate the effectiveness of the test compounds. Results: Results demonstrated a significant reduction in the impact of scopolamine administration on behavioral tasks at a dose of 20 mg/kg for both compounds. Correspondingly, neurochemical assays corroborated these findings. In silico docking analysis on rat butyrylcholinesterase (BChE) was performed to elucidate the binding mode of the compounds. Subsequent molecular dynamics studies unveiled the formation of stable complexes between the test compounds and rat BChE. Conclusions: These findings contribute valuable insights into the potential therapeutic role of sulfonamide-based butyrylcholinesterase inhibitors in addressing memory deficits associated with AD, emphasizing their in silico molecular interactions and stability.